A Rare Neurological Complication of Ranolazine - Jahan Porhomayon; Gino Zadeii; Alireza Yarahmadi (Case Reports in Neurological Medicine)
Myoclonus is not a known side effect of ranolazine. We report a case of myoclonus in a 72-year-old female who underwent cardiac catheterization for angina and was started on ranolazine after the procedure. Two days after ranolazine therapy on 1000 mg per day in divided doses, myoclonus developed, which severely impaired her normal activity. Her symptoms resolved 2 days after discontinuation of ranolazine. Ranolazine was resumed after discharge from hospital with recurrent myoclonus after two days of therapy. The causal relationship between ranolazine and myoclonus was suggested by cessation of myoclonus after ranolazine was discontinued.